New N-amino-5-cyano-6-pyridones as antimicrobial small molecules endowed with DNA gyrase a inhibitory activity: design, one-pot synthesis, biological assessment and in silico insights - Omkulthom Al Kamaly; Amel S. Younes; Marwa F. Harras; Rehab Sabour; Aisha A. Alsfouk; Mona H. Ibrahim (BMC Chemistry)
Abstract A set of innovative N-amino-5-cyano-6-pyridones derivatives was developed and produced using one-pot three-component procedures. The evaluated molecules were examined for their antimicrobial efficacy. Based on the acquired findings, most of the investigated compounds had promising antimicrobial properties. Out of these derivatives of 3-cyanopyridine, compounds 3d and 3e exhibited minimum inhibitory concentrations (MIC) of 3.91 µg/mL against E.coli. In vitro evaluation of DNA gyrase A displayed that molecule 3d exhibited promising potency as an inhibitor, with an IC50 value of 1.68 µg/mL compared to ciprofloxacin (IC50 = 0.45 µg/mL). Furthermore, it was observed that molecule 3e exhibited a moderate inhibitory effect, as indicated by its IC50 value of 3.77 µg/mL. A kinetics study conducted to assess the time required to kill E. coli bacteria demonstrated that gentamycin and compounds 3d and 3e exhibited bactericidal effects within a time frame of 90–120 min. Based on the ADME predictions, compounds 3d and 3e are expected to have favorable oral bioavailability and are unlikely to penetrate the blood-brain barrier. Computational mutagenicity and tumorigenicity studies were conducted on compounds 3d and 3e. The molecular docking investigation has conclusively demonstrated the binding of compounds 3d and 3e to the target DNA gyrase A enzyme, further reinforcing the existing data.